2019
DOI: 10.1016/j.scitotenv.2018.08.365
|View full text |Cite
|
Sign up to set email alerts
|

Cork as a sustainable carbon source for nature-based solutions treating hydroponic wastewaters – Preliminary batch studies

Abstract: Reusing by-products is an important strategy to ensure the preservation of natural capital and climate change mitigation. This study aimed at evaluating the potential of cork granulates, a by-product of winery industry, as an organic carbon (OC) source for the treatment of hydroponic wastewaters. First, chemical characterization was performed and discussed. Secondly, batch studies were performed using synthetic hydroponic wastewater to understand the role of particle size (PS), pH and contact time (CT) on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Few studies have shown the potential of using recycled material for structure of green walls such as polyethylene modules [25], recycled PET bottles [26], or cork boards [27]. Nowadays, there is also a great variety of waste materials being tested and validated in terms of their performance to be used as filter media in NBS: cork [28], coconut shell [23], recycled glass beads [29], mix of coir fibber and perlite [30], and crushed autoclaved aerated concrete [31]. One can conclude that creating new applications to waste materials is the basis for the establishment of an integrative urban chain, where the demand for manufactured products and disposal of waste is reduced.…”
Section: Contribution Of Nature-based Solutions Towards Circularitymentioning
confidence: 99%
“…Few studies have shown the potential of using recycled material for structure of green walls such as polyethylene modules [25], recycled PET bottles [26], or cork boards [27]. Nowadays, there is also a great variety of waste materials being tested and validated in terms of their performance to be used as filter media in NBS: cork [28], coconut shell [23], recycled glass beads [29], mix of coir fibber and perlite [30], and crushed autoclaved aerated concrete [31]. One can conclude that creating new applications to waste materials is the basis for the establishment of an integrative urban chain, where the demand for manufactured products and disposal of waste is reduced.…”
Section: Contribution Of Nature-based Solutions Towards Circularitymentioning
confidence: 99%
“…Since it was first described as an adsorbent in 2005, [20] its use in environmental applications for the removal of a variety of organic and inorganic pollutants has gained considerable attention, and a large number of research articles, as well as reviews, covering this approach have been published [17,[21][22][23][24][25][26]. The cork employment in sample preparation for microextraction purposes was firstly reported in…”
Section: Corkmentioning
confidence: 99%
“…Therefore, its formidable characteristics are promising resources with potential application on adsorption technologies [18]. Herewith cork is a natural, cheap, renewable, fully sustainable, and biodegradable raw material with a very relevant advantage over other carbonaceous materials to be explored as a sorbent in many applications [19].Since it was first described as an adsorbent in 2005, [20] its use in environmental applications for the removal of a variety of organic and inorganic pollutants has gained considerable attention, and a large number of research articles, as well as reviews, covering this approach have been published [17,[21][22][23][24][25][26]. The cork employment in sample preparation for microextraction purposes was firstly reported in…”
mentioning
confidence: 99%
“…Number of papers References 2019 8 [8], [37], [38], [39], [40], [41], [42], [43] 2018 23 [3], [7], [31], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [ literature review. Fig.…”
Section: Yearmentioning
confidence: 99%